Mineral element content of oats (Avena sativa L.) in an acid sulphate soil area of Tupos village, northern Finland - Markku Yli-Halla; Jukka Palko (Scientific Agricultural Society of Finland, 1987)
The mineral element content of oat grains grown in acid sulphate soils (n = 35) and other soils (n = 19) in Tupos was studied. In terms of P, K, Ca, Mg, S, Cu and Zn concentrations, Tupos oats did not differ from the averages and ranges presented for Finnish oats in other studies. Instead, Tupos oats were in general rich in Fe and Co and low in Se. High concentrations of Mn and Ni occurred in samples originating from acid sulphate soils. The lower the soil pH, the higher were the concentrations of Ni and Co in oats. Na and Ni were the only elements displaying a clear relationship between the concentration of the element in oats and the amounts of the element easily soluble in the soil. Tupos oats deviated less than Tupos timothy from the mineral contents of both these plant species usually reported in Finland.